Development of Local Culture-Based Digital Storytelling Media as a Preventive Strategy for Juvenile Delinquency - Fauzi Kurniawan; Anugrah Setiawan; Ibnu Hajar; Anifah; Vidya Dwi Amalia Zati; Marisa Almarind; Fira Aprilia (PT. Global Research Collaboration, 2026)
Juvenile delinquency among adolescents has become a growing concern in non-formal educational environments, particularly due to negative social influences, weak parental supervision, and limited understanding of moral and cultural values. This study aims to develop and evaluate local culture-based digital storytelling media as a preventive strategy against juvenile delinquency among adolescents at the Laskar Pelangi Community Learning Center (PKBM). The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation phases. The participants were 30 adolescents aged 10–15 years selected through purposive sampling. Data were collected through pre-test and post-test questionnaires, observation sheets, and expert validation, and analyzed using normality tests, paired-sample t-tests, and linear regression analysis. The findings revealed that the developed digital storytelling media effectively improved participants’ understanding of moral values, cultural awareness, and social behavior. The paired-sample t-test showed a significant difference between pre-test and post-test scores (Sig. = 0.000 < 0.05), while the regression analysis indicated that the media significantly contributed to juvenile delinquency prevention, with a coefficient of determination (R²) of 79%. In addition, participant engagement reached 85%, indicating strong interest and active involvement during the learning process. The study concludes that local culture-based digital storytelling is an effective and engaging educational medium for strengthening character education, promoting cultural identity, and reducing tendencies toward juvenile delinquency among adolescents in non-formal education settings.